Evaluation of economic, social and sector impacts of agricultural land loss - Iacopo Bernetti; Veronica Alampi Sottini; Augusto Marinelli; Nicola Marinelli; Enrico Marone; Silvio Menghini; Sandro Sacchelli; Gabriele Scozzafava (Italian Journal of Agronomy)
Throughout Italy, soil sealing has had a significant impact on the landscape and on agricultural land. This issue needs to be analyzed in order to provide the policy maker with strategic information for rational land planning and environmental management. In this context, the purpose of this study is to widen our knowledge about the consumption of agricultural land in Italy, analyzing its dynamics, causes and impact. The analysis considers three specific aspects: design of a territorial model to study the extent of land consumption, qualitativequantitative evaluation and classification of the ways in which sealing areas are extended, and analysis of impact and driving forces. The results have helped identify the extent of soil sealing on a geographical basis and, at the same time, to understand how artificialization morphotypologies are linked to the changes that take place and what impact these changes have in relation to territorial multifunctionality and hydrogeological risk.